Spectrum of Orofacial Manifestations in Renal Diseases - Sunil, MK; Kumar, Raghav; Sawhney, Hemant; Gaur, Bosky; Rastogi, Trisha (Journal of Orofacial Research, 2012)
An increasing number of Indians are living with renal disease. This disease has many implications for, in terms of oral manifestations and management of afflicted patients. Renalfailure can give rise to a large spectrum of oral manifestations, affecting the hard or soft tissues of the mouth. The dental care of these patients can be complex, given the medicationsassociated with the disease and the medical conditions that result from inadequately functioning kidneys. Thus, the role of dentist is pivotal in overall health care of patients with renal disease. The authors present relevant information to help dentists in treating patients who exhibit the oral and systemic manifestations of renal disease. The present article reviews, indetail, the current knowledge of the oral and dental aspects of renal failure.